Adsorption isotherm and surface analysis for the carbonate formation on nano Coral shaped Iron((III) Oxide - Lahuri, Azizul Hakim; Yarmo, Mohd Ambar; Nordin, Norazzizi; Dzakaria, Norliza; Adeline Hwong, Ing Ing; Stanley Kuda, Sophia Jelina (Penerbit Universiti Kebangsaan Malaysia, 2023)
The ±-Fe2O3 was synthesized using the hydrolysis method to obtain the nano coral shaped morphology. The adsorption isotherm and surface analysis upon CO2 adsorption were identified. The adsorption capacity for nano coral shaped ±-Fe2O3 was measured at 8.66 cm3/g (17.00 mg/g). Experimental data from CO2 adsorption isotherm at 25 „ƒ best fits with the Freundlich isotherm model which implies the adsorption process is favorable and the multilayer adsorption on the heterogeneous surface. A decrease in the ±-Fe2O3 crystallite peaks in the X-ray diffractogram after the CO2 adsorption was associated with the carbonate complexes species formation. IR spectra indicate higher intensities over the CO2 exposure time of 4, 12 and 24 hours, especially at absorption bands 1041 and 1627 cm-1 that corresponded to C-O and asymmetry O-C-O stretches respectively for carbonate. The morphology of the carbonate formation on nano coral shaped ±-Fe2O3 over the CO2 exposure time was analyzed using FESEM-EDX. Although the carbonate formation was not distinct, the increment in the C element also confirmed the capability of the ±-Fe2O3 in adsorbing CO2 for a long adsorption time of 24 hours.